Avaliação do Sistema de Monitoramento Computadorizado de Digestão in Vitro. 3. Desaparecimento da Matéria Seca e/ou FDN pela Produção de Gás - De Campos, Fábio Prudêncio [UNESP] (2000)
The objective of this work was to evaluate the computerised monitoring of the in vitro gas production system and to compare with in vivo and in situ methods. In the degradation methods, corn silage samples with high/low dry matter (DM) contents, with/without inoculate, were used. Evaluating the silage degradation, by the gas production on the fermentation, the results of the extension of degradation (A+D) were 21.5; 22.6; 22.1 and 20.9 mL of gas/100 mg DM, without significant difference. The coefficients for determination obtained on the total gas production in relation to the potential degradation obtained in situ showed to be high for inoculated corn silage with high DM (R 2 = 0.99), non-inoculated corn silage high DM (R 2 = 0.98), inoculated corn silage with low DM (R 2 = 0.94) and non-inoculated corn silage with low DM (R 2 = 0.93). The DM and/or neutral detergent fiber (NDF) disappearance, determined by gas production in the in vitro/gas system, presented similar results when comparing the others evaluated methods.